EVALUATION OF SERUM PROLACTIN LEVEL IN CIRRHOSIS OF LIVER AND ITS CORRELATION WITH CHILD-TURCOTTE-PUGH SCORE - GOYAL, ADITYA; BANSAL, PANKAJ; DEEPAK, ABHISHEK (International Journal of Current Pharmaceutical Research, 2025)
Objective: The objective of this study was to determine serum prolactin levels in patients with liver cirrhosis and evaluate its correlation with the Child-Turcotte-Pugh (CTP) score. Methods: This observational cross-sectional study was conducted at the Department of General Medicine, School of Medical Sciences and Research, Sharda University, Greater Noida. A total of 50 cirrhotic patients fulfilling the inclusion criteria were enrolled. Each participant provided informed consent, followed by a detailed clinical assessment and biochemical tests. Results: The majority of patients fell within the 41–50 age group. Alcohol was identified as the most prevalent cause of cirrhosis, followed by Hepatitis B virus (HBV), Hepatitis C virus (HCV), and Non-Alcoholic Steatohepatitis (NASH). The mean prolactin levels observed for Child-Pugh grades A, B, and C were 25±2.83, 44.30±9.52, and 76.35±33.84 respectively. A statistically significant correlation (p<0.05) was found between prolactin levels and the Child-Pugh score (r=0.42, p=0.002), indicating that higher disease severity corresponded with elevated prolactin levels. Conclusion: Serum prolactin levels demonstrated a strong association with the Child-Pugh score, signifying their potential as an early marker for liver cirrhosis seveCirrhosis of liverrity and prognosis.